2003
DOI: 10.1348/000712603321661886
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into alleged ‘hauntings’

Abstract: In cases of alleged hauntings, a large number of seemingly trustworthy witnesses consistently report experiencing unusual phenomena (e.g. apparitions, sudden changes in temperature, a strong sense of presence) in certain locations. The two studies reported here explored the psychological mechanisms that underlie this apparent evidence of 'ghostly' activity. The experiments took place at two locations that have a considerable reputation for being haunted-Hampton Court Palace (Surrey, England) and the South Brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Efforts should also be made to minimise, or at least standardise between conditions, any potential environmental cues that could bias participant responses. More generally, given that the field intensities (5 mT) and frequency characteristics (8.3-12.2 Hz, sinusoidal) of the MFs used in this study could be reproduced by commonly found electrical equipment and possibly by natural sources, the findings reported here could underlie a variety of anomalous experiences, ranging from 'paranormal' experiences linked to geographical sites [e.g., Wiseman et al, 2003;Braithwaite, 2004] to the relatively strong symptoms reported by self-identified 'electrosensitive' people [Leitgeb and Schröttner, 2003]; in both cases, the diversity of reported effect could relate to the particular interpretive cues available at the MF exposure location and the subjective interpretation of them, rather than being a direct result of the MF itself.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Efforts should also be made to minimise, or at least standardise between conditions, any potential environmental cues that could bias participant responses. More generally, given that the field intensities (5 mT) and frequency characteristics (8.3-12.2 Hz, sinusoidal) of the MFs used in this study could be reproduced by commonly found electrical equipment and possibly by natural sources, the findings reported here could underlie a variety of anomalous experiences, ranging from 'paranormal' experiences linked to geographical sites [e.g., Wiseman et al, 2003;Braithwaite, 2004] to the relatively strong symptoms reported by self-identified 'electrosensitive' people [Leitgeb and Schröttner, 2003]; in both cases, the diversity of reported effect could relate to the particular interpretive cues available at the MF exposure location and the subjective interpretation of them, rather than being a direct result of the MF itself.…”
Section: Discussionmentioning
confidence: 86%
“…Although such fields do affect human physiology and behaviour, the direction of effects is inconsistent [Cook et al, 2002;Leitgeb and Schröttner, 2003] with a range of complex and apparently unrelated behaviours being susceptible, including mental health declines [Beale et al, 1997], pain sensitivity [Papi et al, 1995], 'paranormal' experiences [Wiseman et al, 2002[Wiseman et al, , 2003Braithwaite, 2004], and sleep disturbances [Graham and Cook, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Wiseman et al (2003) study of Hampton Court Palace, the variability in magnetic fields between the reputedly haunted locations and the baseline locations was statistically significant. It was argued that this supports the studies of Persinger and colleagues and lends weight to the plausibility of the neuromagnetic account.…”
Section: Field-based Studiesmentioning
confidence: 98%
“…These factors include; (i) low lighting levels, (ii) ambiguous sources of stimulation (iii) the presence of draughts (iv) room size (v) contextual and suggestive furnishings, and (vi) localised complex magnetic fields (Braithwaite, 2004;2008;Houran, 2000;Lange & Houran, 2001, 1997: Persinger, 1988Persinger & Koren, 2001;Persinger, Koren, & O'Connor, 2001;Persinger, Tiller, & Koren, 2000;Richards, Persinger, & Koren, 1993;Roll & Persinger, 2001;Wiseman, Watt, Greening, Stevens, O'Keeffe, 2002;Wiseman, Watt, Stevens, Greening, O'Keeffe, 2003; see also Brugger, 2001;McCue, 2002; for a discussion).…”
mentioning
confidence: 99%
“…Natural world sounds are considered to be the basis of human music (Fink, 2003;Hickman et al, 2002) and their use has been compared cross culturally (Tuzin, 1984). Sound waves affect extraordinary human psychological and physiological function, to include inaudible low-frequency (infrasonic) (Ashmead and Wall, 2000;Rushforth et al, 2000;Sheppard and Sheppard, 1993;Von Gierke and Nixon, 1976;Wiseman et al, 2003), harmonic resonance (Gaynor, 1999), and repetition of beats (Neher, 1961(Neher, , 1962Rogers, 1976). Binaural beat (Kendall and Martens, 1984;Mills, 1972) and high-frequency (ultrasonic) sound (Tomatis, 1991) are effective means to enhance cognitive function and suppress or mask pain (Gardner and Licklider, 1959).…”
mentioning
confidence: 99%